ПІДХОДИ ДО ВПРОВАДЖЕННЯ ІННОВАЦІЙНИХ ТЕХНОЛОГІЙ В ОСВІТНІЙ ПРОЦЕС ТЕХНІЧНИХ ЗВО - Петрук В. А.,; Гречановська О. В.,; Сабадош Ю. Г., (International Journal of Innovative Technologies in Social Science, 2019)
The article deals with the problems of introduction and perception by students of innovative technologies in the process of studying humanities, fundamental and special disciplines in technical institutions of higher education. The essence of the concept of "pedagogical innovations" is revealed. The author proposes a methodology for conducting preliminary student surveys, which will help in the future planning of classes using innovative technologies. The basis of the survey is psychological and pedagogical tests and conversation with students. Based on such surveys, the authors determine students' motivation to study disciplines, determine the level of communication, and determine the self-esteem of creative potential. Test results are represented by statistics and a comparative histogram. Presentation results allow you to get acquainted with the needs of students while studying in a technical institution of higher education.